Paediatric ganciclovir dosing in extracorporeal membrane oxygenation: Is standard dosing good enough?. (23rd September 2019) - Murphy, Mark; Chamberlain, Andrea; Tang, Peter; Turpin, Brian; Danziger‐Isakov, Lara
Abstract: What is known and objective: Ganciclovir is a first‐line antiviral agent to treat cytomegalovirus disease in immunocomprimised patients. Ganciclovir pharmacokinetics in ECMO is unknown. Case description: A 6‐year‐old with a stage IV extra‐renal rhabdoid tumor with respiratory failure leading to extracorporeal membrane oxygenation had increasing serum CMV DNAemia while on ganciclovir. What is new and conclusion: This is the first case report of ganciclovir pharmacokinetics in either paediatric or adult ECMO populations. Recommended dosing provided a low, subtherapeutic AUC24 with an associated increase CMV viral load. Higher doses of ganciclovir may be required in ECMO patients, especially without concurrent CRRT.